Vasohibin 2 promotes epithelial-mesenchymal transition in human breast cancer via activation of transforming growth factor β 1 and hypoxia dependent repression of GATA-binding factor 3. (1st March 2017) - Tu, Min; Li, Zhanjun; Liu, Xian; Lv, Nan; Xi, Chunhua; Lu, Zipeng; Wei, Jishu; Song, Guoxin; Chen, Jianmin; Guo, Feng; Jiang, Kuirong; Wang, Shui; et al.
Abstract: Vasohibin 2 (VASH2) is identified as an angiogenic factor, and has been implicated in tumor angiogenesis, proliferation and epithelial-mesenchymal transition (EMT). To investigate the EMT role of VASH2 in breast cancer, we overexpressed or knocked down expression of VASH2 in human breast cancer cell lines. We observed that VASH2 induced EMT in vitro and in vivo . The transforming growth factor β1 (TGFβ1) pathway was activated by VASH2, and expression of a dominant negative TGFβ type II receptor could block VASH2-mediated EMT. In clinical breast cancer tissues VASH2 positively correlated with TGFβ1 expression, but negatively correlated with E-cadherin (a marker of EMT) expression. Under hypoxic conditions in vitro or in vivo, we found that down-regulation of estrogen receptor 1 (ESR1) in VASH2 overexpressing ESR1 positive cells suppressed E-cadherin. Correlation coefficient analysis indicated that VASH2 and ESR1 expression were negatively correlated in clinical human breast cancer tissues. Further study revealed that a transcription factor of ESR1, GATA-binding factor 3 (GATA3), was down-regulated by VASH2 under hypoxia or in vivo . These findings suggest that VASH2 drives breast cancer cells to undergo EMT by activation of the TGFβ1 pathway and hypoxia dependent repression GATA3-ESR1 pathway, leading to cancer metastasis. Highlights: VASH2 drives human breast cancer cells to undergo epithelial-mesenchymal transition. VASH2 activates the expression of TGF β1 in human breast cancer. VASH2 suppresses E-cadherin expression in human breast cancer via a hypoxia dependent down-regulation of GATA3 and ESR1.